PESTEL Analysis Of Waste-to-Energy at TPPAS Regional Nambo - Nusantari, Nurina Khoirunisa (Fakultas Pendidikan Ekonomi dan Bisnis, 2021)
Urbanization and urban development are unavoidable along with the socio-economic development. impact that is a challenge for cities with rapid urbanization, booming economy, the rise in community living standards have increase the amount of waste generation. Solutions are needed that can reduce the impact and the amount of waste produced. Developing countries such as China, Malaysia, India, Thailand and Indonesia began to see waste-to-energy as one of the solutions. Indonesia has begun to build a waste treatment plant that converts waste into power generation, RDF, or other products that have value. In Indonesia the processing of waste into energy in this case RDF was built in Nambo. However, in the process there are variety issues such as political, economic, social, technological, environmentalÂ and legal. The difficulty often faced such as public opposition, poor decision making, financing and others. This research aims to find out what challenges faced in the development and sustainablity of WTE at TPPAS Regional Nambo using analysis PESTEL. WTE project is one of solution to faced the amount of waste that keep increasing every year, because the amount of waste isnâ€™t balance with landfill area. Besides the processing process produces products that have a sale value.